Cardiovascular Risk Assessment Among Workers in the West Attica Landfill - Vladeni , Z.; Douna, E.; Koupidis, S.; Savourdos, P.; Makrynos, G.; Vitale, E.; Dounias, G. (European Scientific Journal, ESJ, 2025)
Introduction: Landfill workers are frequently exposed to a multitude of deleterious factors that can adversely affect their health. These include environmental contaminants such as dioxins, furans, biogas, and heavy metals, as well as occupational hazards like noise, vibration, and extreme temperatures. Aims and Scope: This pilot study, conducted at the Integrated Solid Waste Management Facility of Fili (OEDA Filis), aimed to measure environmental risk parameters and assess their effects on the cardiovascular health of workers. Method: Data collection involved questionnaires to record personal history, work stress and job positions, clinical examinations, and blood lipid tests. Cardiovascular risk (Heart Score) was evaluated based on standards set by the Hellenic Heart Association, which incorporated the Heart Score using Greek data. Results: The majority of employees at OEDA Filis were married men from lower socioeconomic backgrounds, with 77% reporting no chronic health issues and self-assessing their health status as good. Most subjects had body mass indices categorized as either normal or overweight. Environmental assessments identified elevated concentrations of PM10 and phenanthrene in the workplace, though levels of benzo(a)pyrene and naphthalene were within safety thresholds. About 21% of the workforce was identified as being at considerable risk for cardiovascular disease. No statistically significant relation was found between the Heart Score and job positions (p = 0.3), indicating that occupational role alone does not predict cardiovascular risk. However, elevated Heart Scores were more frequently observed among positions with greater exposure to environmental and occupational hazards. Conversely, office workers, who had reduced exposure to exhaust, noise, and air pollutants, exhibited lower Heart Scores. Univariate analysis showed a significant association between occupational stress and Heart Score (p = 0.037); workers under high stress had significantly lower levels of high-density lipoprotein (HDL) (p = 0.006). Additionally, a significant association existed between the use of personal protective equipment (PPE) and lower Heart Score risk index values (p = 0.012), highlighting the protective impact of PPE in mitigating cardiovascular risk among exposed workers. Conclusion: This study enhances understanding of the associations between cardiovascular risk and exposure to environmental and occupational hazards at landfill sites. It underscores the critical need to establish a specialized observatory for continuous monitoring of occupational health and safety at these locations. Such an observatory should include regular health assessments for workers and systematic monitoring of environmental pollutants. Furthermore, the study advocates for initiatives aimed at improving the cardiovascular health of landfill workers, underscoring their necessity in this high-risk occupational environment.